UCP2 Inhibits ROS-Mediated Apoptosis in A549 under Hypoxic Conditions - Deng, Sanming; Yang, Ye; Han, Yong; Li, Xiaofei; Wang, Xiaoping; Li, Xueyong; Zhang, Zhipei; Wang, Yunjie (PLOS ONE, 2012)
The Crosstalk between a tumor and its hypoxic microenvironment has become increasingly important. However, the exact role of UCP2 function in cancer cells under hypoxia remains unknown. In this study, UCP2 showed anti-apoptotic properties in A549 cells under hypoxic conditions. Over-expression of UCP2 in A549 cells inhibited reactive oxygen species (ROS) accumulation (P<0.001) and apoptosis (P<0.001) compared to the controls when the cells were exposed to hypoxia. Moreover, over-expression of UCP2 inhibited the release of cytochrome C and reduced the activation of caspase-9. Conversely, suppression of UCP2 resulted in the ROS generation (P = 0.006), the induction of apoptosis (P<0.001), and the release of cytochrome C from mitochondria to the cytosolic fraction, thus activating caspase-9. These data suggest that over-expression of UCP2 has anti-apoptotic properties by inhibiting ROS-mediated apoptosis in A549 cells under hypoxic conditions.